Preferred vs. actual working hours: A ten years paneleconometric analysis for professions, entrepreneurs and employees in Germany - Joachim Merz; Rainer Lang (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 1997)
Labour market dynamics according the individual working hour tension (preferred working hours minus actual working hours) of active people with focus on the self-employed, as professions and entrepreneurs, and employees are investigated in our study. The individual longitudinal analysis based on panel data allows us to follow the individual process of working time preferences and actual outcomes in its individual convergence/divergence balancing process in the course of time. Our microanalytic and paneleconometric results (with pooled, one and two factor fixed and random effects models) quantify the working hour tension developments and its determinants in a decade from the mid 80s to the mid 90s. Microdata base is the German Socio-Economic Panel with ten waves from 1985 to 1994. Finally, we discuss impacts of our results for labour market strategies and a targeted economic and social policy. – – Die Arbeitsmarktdynamik hinsichtlich der individuellen Arbeitszeit-(An)Spannung (Arbeitszeitwunsch minus Arbeitszeitwirklichkeit) der Erwerbstätigen mit Fokus auf die Selbständigen, als Freie Berufe und Unternehmer, sowie die abhängig Beschäftigten ist das Thema unserer Studie. Die individuelle Längsschnittanalyse auf der Basis von Paneldaten erlaubt es uns, die individuelle Entwicklung zwischen gewünschter und tatsächlicher Arbeitszeit in ihrem Konvergenz/Divergenzprozeß im Wandel der Zeit zu verfolgen. Unsere mikroanalytischen und panelökonometrischen Resultate (mit pooled, ein und zwei Faktor fixed und random Effektmodellen) quantifizieren die Entwicklung und ihre Determinanten in der Dekade von Mitte der 80er bis Mitte der 90er Jahre. Mikrodatenbasis ist das Sozio-ökonomische Panel mit zehn Wellen von 1985 bis 1994. Abschließend diskutieren wir Folgerungen unserer Ergebnisse für Arbeitsmarktstrategien und eine zielgerichtete Wirtschafts- und Sozialpolitik.
Keywords: D1; D3; J21; J22; J23; J44; 330; Labour market dynamics; working hour tension; desired and actual working hours; paneleconometric analyses; professions; entrepreneurs and employees; Arbeitsmarktdynamik; Arbeitsmarkt(an)spannung; gewünschte und tatsächliche Arbeitszeit; panelökonometrische Analysen; Freie Berufe; Unternehmer und abhängig Beschäftigte